Human T-cell lymphotropic virus in patients infected with HIV-1: molecular epidemiology and risk factors for transmission in Piaui, Northeastern Brazil - de Oliveira, Evaldo H; Oliveira-Filho, Aldemir B; Souza, Lucinda A; da Silva, Letiano V; Ishak, Marluísa O G; Ishak, Ricardo; Vallinoto, Antonio C R (Current HIV research, 2012)
This study aimed to describe the epidemiological, immunological and molecular features of infection by the human T-lymphotropic virus-1/2 (HTLV-1/2) in individuals with HIV-1 in an urban area of Piaui State, Brazil. Exclusion criteria included patients under 18 years of age, pregnant women or Amerindians. Of 805 individuals analyzed by the serological method (ELISA) for the detection of anti-HTLV-1/2, 18 (2.24%) were positive, but only 13 (1.61%) were confirmed by PCR. The RFLP analysis revealed that nine (1.12%) of these subjects were positive for HTLV-1 and four (0.5%) for HTLV-2. The mean age of these co-infected individuals was 50.9±9.1 years, and a significant association was found with age (above 40 years: p = 0.002), minor surgeries (p = 0.004) and blood transfusion (p = 0.031). Quantification of the T CD4+/CD8+ lymphocytes and the HIV-1 viral load showed no significant association of T CD8 + lymphocyte levels with co-infection in the patients with HIV-1/HTLV-1. The sequencing of the LTR region and phylogenetic analysis indicated that the nine HTLV-1 strains belong to the Transcontinental subgroup of the Cosmopolitan group (1a), with a 83% (neighbor-joining) bootstrap value. The HTLV-2 strains were identified as subtype HTLV-2c, supported by a bootstrap value of 79%. Further studies in other population subgroups, such as blood donors and drug users, will be necessary to clarify the dissemination of HTLV-1/2 in Piau and elucidate the developmental profile of the virus in the region.